The 1987 Mexican Disinflation Program : An Exchange-Rate-Based Stabilization? - Santaella, Julio; Vela, Abraham (Washington, D.C. : International Monetary Fund, 1996)
We examine whether Mexico's disinflation experience during 1987-94 fits a widely accepted set of stylized facts of exchange rate-based stabilization (ERBS), and relate it to theories put forward to account for the boom-recession business cycle associated with ERBS. A cursory look at Mexican data shows that the experience fits quite closely the theoretical predictions and the stylized facts of ERBS. However, the paper shows that there were some important differences and peculiarities of the Mexican case that deserve further study, especially regarding the role of the nominal anchor and the nature of the business cycle.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet